INVESTASI PENDIDIKAN MEMUTUS RANTAI KEMISKINAN DI SULAWESI SELATAN - Bayu Rhamadani Wicaksono; Muhammad Aliem (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2022)
The development in all sectors is being intensively carried out by the regional government for the community welfare, including in the scope of South Sulawesi Province. The development is not only in monumental forms, such as infrastructures, but also building human resources, such as investment in education sector. The education investment is expected to be able to break the chain of poverty that is still shackling. This study aims to analyze the relationship between education and poverty in South Sulawesi. The data used are data from 24 districts/municipalities in South Sulawesi 2017-2019 analyzed using panel data regression with the Random Effects Model (REM) and the results are as follows. The variables of Gross Enrollment Rate (GER) in high school and literacy rate have a negative and significant effect on poverty rate in South Sulawesi. Meanwhile, the variable of Net Enrollment Rate (NER) in high school has a negative but not significant effect on poverty rate in South Sulawesi. Hopefully, the government can continue the good policies in education sector, so it can give the community equal opportunities to access education.